Efficacy and Mechanisms of Gastric Volume-Restriction Bariatric Devices - Wang, Yanmin; Kassab, Ghassan S. (Frontiers in Physiology, 2021)
Obesity is a chronic disease that affects over 795 million people worldwide. Bariatric surgery is an effective therapy to combat the epidemic of clinically severe obesity, but it is only performed in a very small proportion of patients because of the limited surgical indications, the irreversibility of the procedure, and the potential postoperative complications. As an alternative to bariatric surgery, numerous medical devices have been developed for the treatment of morbid obesity and obesity-related disorders. Most devices target restriction of the stomach, but the mechanism of action is likely more than just mechanical restriction. The objective of this review is to integrate the underlying mechanisms of gastric restrictive bariatric devices in morbid obesity and comorbidities. We call attention to the need for future studies on potential mechanisms to shed light on how current gastric volume-restriction bariatric devices function and how future devices and treatments can be further improved to combat the epidemic of obesity.